The Tragic Error of Progeny-eating in Ancient Greek and Chinese Tradition - Xue, Rongzhen (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2026)
This dissertation examines how progeny-eating is narratively shaped into an extreme ethical transgression in ancient Greek and Chinese traditions. It asks why some Greek narratives routinely stage progeny-eating in close conjunction with incest within a self-reinforcing cyclical structure of kinship violation and retaliatory justice, whereas Chinese accounts detach progeny-eating from the idiom of impurity and instead rationalise it within political ethics and sovereign legitimacy. Employing a comparative framework that integrates semantic analysis, narratology, and intellectual history, this study traces how progeny-eating is conceptualised and made intelligible within distinct moral vocabularies and narrative structures. Rather than treating hamartia as a cross-cultural category, it is examined as a specifically Greek term whose tragic purchase can be set against Chinese idioms of fault and accountability. Chapter One analyzes Greek error terms (e.g. hamartia, adikia), outlining a layered account of agency and responsibility. Chapter Two examines Chinese terms (cuo, wu, guo, sheng, shi, jiu), and situates them within Confucian, Legalist, and Daoist approaches to normative failure. Chapter Three examines the ritual-narrative logic that couples progeny-eating with incest in Greek tragedy, with miasma functioning as a structural hinge. Chapter Four reconstructs the reception of Wenwang’s progeny-eating and its ideological transformation within Confucian ethics. Chapter Five offers a comparative synthesis on impurity, the body, normativity, and heroism. Ultimately, the dissertation argues that ethical extremity is managed through divergent cultural mechanisms, and that treating “tragic error” as a universal template risks imposing a Eurocentric grid on non-Greek materials. By juxtaposing Thyestes’ hamartia with Chinese cannibalism narratives, it shows that Greek tragedy frames progeny-eating through a logic of transgressive kinship and retaliatory justice, anchoring extreme violations in sustained moral–ethical tension; whereas Chinese texts more often detach such acts from moral decline and re-situate them within secular historiography, political order, and sovereign virtue. The study thus clarifies how different traditions delineate—and narratively stabilise—the limits of ethical imagination.
APPROVED
Keywords: Hamartia; Tragic Error; Progeny-eating; Cannibalism; Sino-Hellenic Comparison